RANCANG BANGUN APLIKASI AUGMENTED REALITY MEDIA PEMBELAJARAN PENGENALAN MACAM-MACAM BOLA PADA ANAK USIA DINI - Raharja, Pradana Ananda; Indrajaya, Rochmat (Universitas Lancang Kuning, 2023)
Learning activities for the introduction of various balls are currently still using book media. However, book media has a reading mandate that is still relatively lacking due to the objects displayed in books that are not as real and have less impact on children at an early age. Augmented Reality integrates the virtual world with the natural world built by humans on a computer system. The method chosen in this study is to apply the prototype method. This method was chosen because it has the advantage of realising user needs easier. Testing the functionality of this application is selected by the black box testing method. Using this black box test method, all the functions in the AR Bola application can work as they should. In addition to the black box method, the System Usability Scale (SUS) test method was also carried out. The test results using the SUS questionnaire obtained an average score of 83. This was included in the